Pediatric Acute Myocarditis With Short-Term Outcomes and Factors for Extracorporeal Membrane Oxygenation: A Single-Center Retrospective Cohort Study in Vietnam - Tuan, Ta Anh; Xoay, Tran Dang; Phuc, Phan Huu; Hung, Dau Viet; Dung, Nguyen Trong; Truong, Nguyen Ly Thinh; Thuan, Nguyen Van; Dien, Tran Minh (Frontiers in Cardiovascular Medicine, 2021)
Objective: Data on the management and outcomes of acute myocarditis treated with extracorporeal membrane oxygenation (ECMO) among low- and middle-income countries are limited. This study aimed to determine the short-term outcomes and also identify factors associated with ECMO use among children with acute myocarditis at a tertiary children's hospital in Vietnam. Methods: A single-center, retrospective observational study was conducted between January 2016 and February 2021. Pediatric patients with acute myocarditis, aged 1 month to 16 years, were included. Results: In total, 54 patients (male, 46%; median age, 7 years) with acute myocarditis were included; 37 of them received ECMO support. Thirty percent (16/54) of the patients died, and 12 of them received ECMO. Laboratory variables that differed between survivors and non-survivors included median left ventricular ejection fraction (LVEF) at 48 h (42 vs. 25%; p = 0.001), platelet count (304 g/L [interquartile range (IQR): 243–271] vs. 219 g/L [IQR: 167–297]; p = 0.014), and protein (60 g/dl [IQR: 54–69] vs. 55 [IQR: 50–58]; p = 0.025). Among patients who received ECMO, compared with the survivors, non-survivors had a low LVEF at 48 h (odds ratio (OR), 0.8; 95% confidence interval (CI): 0.6–0.9; p = 0.006) and high vasoactive-inotropic score (OR, 1.0; 95% CI: 1.0–1.0; p = 0.038) and lactate (OR, 2.8; 95% CI, 1.2–6.1; p = 0.013) at 24 h post-ECMO. Conclusions: The case fatality rate among children with acute myocarditis was 30 and 32% among patients requiring ECMO support. Arrhythmia was an indicator for ECMO in patients with cardiogenic shock.